SISTEM INFORMASI FORECASTING DATA PENJUALAN KENDARAAN MENGGUNAKAN METODE SINGLE EXPONENTIAL SMOOTHING (STUDI KASUS: PT. SENDANG SUMBER ARUM VIAR MOTOR CIREBON) - Lestari, Lina; Lena Magdalena; Mesi Febima (Universitas Methodist Indonesia, 2024)
Limited Liability Companies (PT) are found in almost all regions in Indonesia, one of which is PT. Sendang Sumber Arum 'VIAR Motor which provides sales of Karya 3-wheeled motorcycle units, e-motorcycles, razors, Cross Adventure, vintech, and e-bikes. E-bikes are the best-selling vehicles for each period, especially the UNO3 type. The problem faced by this company is the imbalance in sales figures which causes damage to the e-bike batteries that are sold over a long period of time and requires forecasting. The Single Exponential Smoothing method is the right forecasting method used to predict demand for goods that change very quickly, which aims to determine the estimated availability of vehicle units that must be held in the future, based on previous sales data. In determining the error value in forecasting, the author uses the Mean Square Error (MSE) which is based on the alpha value. This forecasting is implemented into an information system that produces a forecast for the UNO3 type e-bike with the smallest Mean Square Error (MSE) value obtained with an alpha of 0.3, namely with a value of 167.294. This proves the best forecast for predicting the quantity of UNO3-type e-bike stock units at PT. Sendang Sumber Arum ‘VIAR Motor’ Cirebon for the period of June 2024 using alpha 0.3. So the forecast value of UNO3 type e-bike unit sales for June 2024 in the 11-month forecast period with alpha 0.3 is 24.89 or around 25 units with actual data.